Aluminum alloy material and method for manufacturing the same, aluminum alloy member and method for manufacturing and using the same

CN122879558APending Publication Date: 2026-10-09CHINALCO RES INST OF SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611103405.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]鉴于背景技术中存在的技术问题,本发明提供了一种铝合金材料及其制备方法、铝合金构件及其制备方法和应用,旨在解决现有Al-Ce系铝合金粉末材料经增材制造成形后,难以在获得高致密成形的基础上,同时兼顾较好的25℃力学性能和高温力学性能的问题

Benefits of technology

[0017]根据本发明的第五个方面,提供了一种航空航天材料,航空航天材料包括上述的铝合金构件或者上述的铝合金构件的制备方法制备得到的铝合金构件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879558A_ABST
    Figure CN122879558A_ABST
Patent Text Reader

Abstract

The application provides an aluminum alloy material and a preparation method thereof, an aluminum alloy component and a preparation method and application thereof, and relates to the technical field of aluminum alloys. The aluminum alloy material comprises, in percentage by weight: Ce 6.0%-11.0%, Er 0.6%-0.8%, Sc 0.5%-0.8%, Zr 0.3%-0.4%, and the balance of Al and inevitable impurities; wherein the volume fraction of particles with a particle size in the range of 15-70 mu m in the aluminum alloy material is greater than or equal to 90%. The technical scheme of the application can effectively solve the problem that an existing Al-Ce series aluminum alloy material is difficult to obtain high-density forming, good mechanical properties at 25 DEG C and high-temperature mechanical properties after additive manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, specifically to an aluminum alloy material and its preparation method, an aluminum alloy component and its preparation method, and its application. Background Technology

[0002] Aluminum alloys are characterized by low density, high specific strength, and good machinability, and are widely used in aerospace, defense, high-end transportation, and new energy vehicles. As these fields place higher demands on the load-bearing capacity, service temperature, and structural complexity of lightweight structural components, aluminum alloy materials that combine high strength and toughness with high heat resistance are receiving increasing attention.

[0003] Additive manufacturing, also known as 3D printing, is a manufacturing technology that forms three-dimensional solid components by depositing materials layer by layer. Selective laser melting (SLM) is a crucial technology in metal additive manufacturing, capable of fabricating complex aluminum alloy components through layer-by-layer powder deposition and melting. However, aluminum alloys undergo rapid melting, rapid solidification, and repeated thermal cycling during laser additive manufacturing, which can easily lead to defects such as hot cracks, porosity, and residual stress, thus affecting the density and mechanical properties of the aluminum alloy components. While the formability of some aluminum alloys can be improved through composition adjustment or process optimization, their strength, plasticity, and high-temperature service performance still struggle to simultaneously meet the requirements of high-end heat-resistant load-bearing structural components.

[0004] Currently, aluminum alloy powders used in additive manufacturing mainly include Al-Si, Al-Cu, Al-Mg, and Al-Zn-Mg-Cu alloy powders. Al-Si alloy powders have good formability, but the strengthening phase tends to coarsen under high-temperature service conditions, leading to a decrease in strength. Although Al-Cu alloys can achieve a certain strength, the stability of the strengthening phase is insufficient under long-term high-temperature conditions, and the material properties are prone to degradation. In Al-Mg alloys, the Mg element is prone to volatilization and oxidation during laser forming, which can easily cause compositional fluctuations and porosity defects. Al-Zn-Mg-Cu alloys have high strength, but they are highly sensitive to hot cracking, making additive manufacturing difficult, and their heat resistance is still insufficient.

[0005] In recent years, Al-Ce aluminum alloys have attracted attention due to their low susceptibility to hot cracking and certain heat resistance potential. Al-Ce aluminum alloys are less prone to coarsening or dissolution at higher temperatures, which helps improve the high-temperature performance of aluminum alloys. However, existing Al-Ce aluminum alloys still struggle to simultaneously achieve high formability, high strength, high plasticity, and high heat resistance. For example, while some Al-Ce aluminum alloys can achieve high strength at 25°C, their elongation is low, making it difficult to meet the application requirements of high-strength and high-toughness structural components; while some Al-Ce aluminum alloys possess certain heat resistance, their plasticity retention under high-temperature conditions remains unsatisfactory; and while some Al-Ce aluminum alloys can achieve high formability, their mechanical properties at 25°C and high-temperature mechanical properties are still unsatisfactory, especially the difficulty in simultaneously maintaining strength and plasticity under high-temperature conditions, failing to meet the requirements of high reliability and high-temperature service stability for aerospace components. Summary of the Invention

[0006] In view of the technical problems existing in the background art, the present invention provides an aluminum alloy material and its preparation method, an aluminum alloy component and its preparation method and application, aiming to solve the problem that it is difficult to obtain high density forming of existing Al-Ce aluminum alloy powder materials by additive manufacturing, while simultaneously taking into account good mechanical properties at 25°C and high temperature mechanical properties.

[0007] To achieve the above objectives, according to one aspect of the present invention, an aluminum alloy material is provided, comprising, by weight percentage: Ce 6.0%~11.0%, Er 0.6%~0.8%; Sc 0.5%~0.8%, Zr 0.3%~0.4%, with the balance being Al and unavoidable impurities; wherein, in the aluminum alloy material, the volume fraction of particles with a particle size in the range of 15μm~70μm is ≥90%.

[0008] Furthermore, the weight ratio of Er to Sc is (0.8~1.5):1.

[0009] Furthermore, the volume distribution D10 particle size of the aluminum alloy material is 15μm~25μm, the volume distribution D50 particle size is 30μm~40μm, and the volume distribution D90 particle size is 55μm~70μm.

[0010] Furthermore, the sphericity of the aluminum alloy material is ≥80%, and the hollow powder rate is ≤1%; and / or, the oxygen content of the aluminum alloy material is ≤300ppm, and the nitrogen content is ≤20ppm.

[0011] According to a second aspect of the present invention, a method for preparing an aluminum alloy material is provided, comprising the following steps: S1, mixing the raw materials for forming the aluminum alloy material according to a ratio to obtain a mixture; S2, subjecting the mixture to a melting process, a refining process, an atomization process, and a cooling process in sequence to obtain aluminum alloy powder; S3, sieving the aluminum alloy powder to obtain the aluminum alloy material.

[0012] Furthermore, the melting temperature is 750℃~800℃ and the melting time is 20min~30min; and / or, the refining temperature is 1000℃~1050℃ and the refining time is 15min~20min; and / or, the atomization temperature is 850℃~900℃ and the atomization pressure is 2.0MPa~3.3MPa.

[0013] According to a third aspect of the present invention, a method for preparing an aluminum alloy component is provided, the method comprising: using the aluminum alloy material described above, or the aluminum alloy material prepared by the method described above, sequentially performing 3D printing and heat treatment to obtain the aluminum alloy component.

[0014] Furthermore, the 3D printing is carried out in an atmosphere with an oxygen content of ≤0.05%; and / or, the 3D printing pressure is 23mbar~27mbar, and the fan flow rate is 2.5m / s~3.0m / s; and / or, the substrate preheating temperature is 80℃~150℃; and / or, the 3D printing layer thickness is 20μm~50μm, and the interlayer rotation angle is 67°; and / or, the laser scanning spacing is 90μm~110μm, the laser scanning power is 250W~330W, and the laser scanning speed is 1000mm / s~2000mm / s.

[0015] Furthermore, the heat treatment temperature is 320℃~350℃, and the heat treatment time is 4h~7h.

[0016] According to a fourth aspect of the present invention, an aluminum alloy component is provided, which is prepared by the above-described method for preparing aluminum alloy components; wherein the aluminum alloy component has a tensile strength of 520 MPa to 550 MPa at 25°C, a yield strength of 440 MPa to 460 MPa at 25°C, and an elongation of 10.5% to 13.5% at 25°C; a tensile strength of 250 MPa to 280 MPa at 300°C, a yield strength of 230 MPa to 260 MPa at 300°C, and an elongation of 16.2% to 18.3% at 300°C; and a tensile strength of 180 MPa to 200 MPa at 400°C, a yield strength of 150 MPa to 180 MPa at 400°C, and an elongation of 16.5% to 19.2% at 400°C.

[0017] According to a fifth aspect of the present invention, an aerospace material is provided, comprising the aluminum alloy component described above or an aluminum alloy component prepared by the method described above.

[0018] By applying the technical solution of this invention, and controlling the weight percentages of Ce, Er, Sc, and Zr, as well as the volume fraction of the aluminum alloy material within the particle size range of 15 μm to 70 μm, the alloy components are synergistically combined. Ce, in particular, contributes to the formation of highly thermally stable Al. 11 The Ce3 and Al2Ce phases pin grain boundaries and improve near-eutectic solidification characteristics, thereby reducing hot cracking susceptibility. Er and Sc synergistically form Al3(Er,Sc,Zr) composite nanoprecipitates. The relatively fast-diffusion Er and Sc contribute to the formation of Er-rich and Sc-rich cores, while Zr, due to its slow diffusion, forms a dense Zr-rich shell outside the core, thus forming a core-shell composite nanoprecipitate. This helps suppress the diffusion of Sc and Er atoms, significantly delaying high-temperature coarsening of the precipitates. Furthermore, a suitable particle size distribution helps improve powder spreading uniformity and laser melting stability, reducing forming defects such as porosity, lack of fusion, and cracks. Therefore, the aluminum alloy material of this invention, after additive manufacturing, can achieve high-density forming while simultaneously maintaining good tensile mechanical properties at 25°C and high-temperature tensile mechanical properties, thus meeting the application requirements of lightweight, high-reliability, and high-temperature service stability aluminum alloy components in aerospace, defense, high-end transportation, and new energy vehicle fields. Attached Figure Description

[0019] Figure 1 This is an optical microscope metallographic image of the aluminum alloy component obtained in Embodiment 2 of the present invention;

[0020] Figure 2 This is an optical microscope metallographic image of the aluminum alloy component obtained in Example 6 of the present invention;

[0021] Figure 3This is an optical microscope metallographic image of the aluminum alloy component obtained in Example 14 of the present invention;

[0022] Figure 4 This is an optical microscope metallographic image of the aluminum alloy component obtained in Example 18 of the present invention;

[0023] Figure 5 This is an optical microscope metallographic image of the aluminum alloy component obtained in Comparative Example 1 of the present invention;

[0024] Figure 6 This is an optical microscope metallographic image of the aluminum alloy component obtained in Comparative Example 4 of the present invention. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0026] As described in the background section of this invention, existing technologies suffer from the problem that, after additive manufacturing, Al-Ce aluminum alloy powder materials are difficult to achieve both high-density forming and good mechanical properties at 25°C and high-temperature mechanical properties. To address this issue, in a typical embodiment of this invention, an aluminum alloy material is provided, comprising, by weight percentage: Ce 6.0%~11.0%, Er 0.6%~0.8%; Sc 0.5%~0.8%, Zr 0.3%~0.4%, with the balance being Al and unavoidable impurities; wherein, in the aluminum alloy material, the volume fraction of particles with a particle size in the range of 15μm~70μm is ≥90%.

[0027] The aluminum alloy material of this invention is mainly used in additive manufacturing, especially laser powder-layout additive manufacturing, for the fabrication of aluminum alloy components with complex structures in aerospace, defense, high-end transportation, and new energy vehicles. During additive manufacturing, the aluminum alloy material typically undergoes powder laying, rapid laser melting, rapid solidification, and repeated thermal cycling. Its composition and powder characteristics directly affect the thermal cracking sensitivity, powder melting sufficiency, and the formation of defects such as porosity and cracks during the forming process, further influencing the forming density and final mechanical properties of the aluminum alloy component. Therefore, the aluminum alloy material not only needs to possess good high density and low-defect forming adaptability, but also needs to ensure that the formed aluminum alloy component has good mechanical properties at 25°C and high-temperature mechanical properties, thereby meeting the application requirements of lightweight, heat-resistant, and load-bearing structural components in aerospace, defense, high-end transportation, and new energy vehicles.

[0028] The aluminum alloy material of this invention achieves a synergistic effect between compositional and powder property regulation by controlling the weight percentages of Ce, Er, Sc, and Zr, as well as the powder particle size distribution. Ce primarily forms a stable, heat-resistant strengthening phase and improves solidification characteristics during additive manufacturing. Er, Sc, and Zr collectively form Al3(Er,Sc,Zr) composite nanoprecipitates, enhancing the strength and high-temperature structural stability of the aluminum alloy components. A suitable powder particle size distribution improves powder spreading uniformity and laser melting stability. This allows the aluminum alloy material, after additive manufacturing, to achieve both high density and good mechanical properties at 25°C and at high temperatures.

[0029] Specifically, Ce is an important heat-resistant element in the aluminum alloy material of this invention. The addition of Ce allows it to form Al with Al. 11 Intermetallic compounds with high thermal stability, such as Ce3 and Al2Ce, do not readily coarsen or dissolve at high temperatures, allowing them to function as stable heat-resistant strengthening phases within the α-Al matrix. On one hand, when these phases are distributed within the α-Al matrix grains, they hinder local slip and deformation propagation, increasing the external force required for plastic deformation in aluminum alloy components, thus contributing to improved strength. On the other hand, when these phases are distributed near the grain boundaries of the α-Al matrix, they restrict grain boundary migration during heat treatment or high-temperature service, inhibiting continuous grain growth and reducing coarsening of the aluminum alloy microstructure under high-temperature conditions, thus maintaining a relatively fine and stable microstructure. Therefore, the heat-resistant strengthening phase formed by Ce can improve the strength of aluminum alloy components while simultaneously enhancing high-temperature structural stability, providing support for the high-temperature performance of aluminum alloy materials.

[0030] Meanwhile, the Al-Ce system exhibits near-eutectic solidification characteristics, a narrow solidification temperature range, and good liquid phase fluidity. In additive manufacturing processes such as selective laser melting, these solidification characteristics help improve the feeding capacity and microstructure formation during molten pool solidification, reduce hot cracking sensitivity, and decrease the generation of forming defects such as cracks. Based on this, this invention, by controlling the Ce element weight percentage to 6.0%~11.0%, can effectively support the high-temperature microstructure stability and low hot cracking sensitivity of Ce, while mitigating the problems caused by insufficient heat-resistant strengthening phases due to excessively low Ce content, and the problems caused by excessive formation of intermetallic compounds, decreased microstructure coordination of aluminum alloys, or increased preparation costs due to excessively high Ce content. This helps to balance additive manufacturing compatibility and high-temperature tensile mechanical properties.

[0031] Er, Sc, and Zr are composite microalloying elements in the aluminum alloy material of this invention. When added together, they can participate in the formation of Al3(Er,Sc,Zr) composite nanoprecipitates during subsequent heat treatment, resulting in a fine, dispersed, and thermally stable strengthening structure within the α-Al matrix. When this composite nanoprecipitate is distributed within the α-Al matrix, it increases the difficulty of local slippage and deformation propagation within the α-Al matrix, thereby improving the yield strength and tensile strength of the aluminum alloy component. Simultaneously, this composite nanoprecipitate also helps limit the excessive growth of α-Al matrix grains during heat treatment or high-temperature service, keeping the aluminum alloy microstructure relatively fine and stable, thus contributing to the aluminum alloy component's ability to maintain both 25°C and high-temperature mechanical properties.

[0032] Specifically, Sc is a commonly used and highly efficient microalloying element in aluminum alloys. Sc can participate in the formation of Al3(Er,Sc,Zr) composite nanoprecipitates and enhance the strengthening effect of these composite nanoprecipitates on the α-Al matrix. After Sc enters the Al3(Er,Sc,Zr) composite nanoprecipitates, it helps to enhance the interaction between the composite nanoprecipitates and the α-Al matrix, making the composite nanoprecipitates more effectively hinder local slip and deformation propagation within the α-Al matrix, thereby giving the aluminum alloy components a higher strength basis. However, Sc is expensive, and relying solely on high Sc content for strengthening would significantly increase the manufacturing cost of aluminum alloy materials, which is not conducive to engineering applications.

[0033] Er can complement Sc in the aluminum alloy material of this invention. On the one hand, Er can enter the Al3(Er,Sc,Zr) composite nano-precipitates, working with Sc to enhance the strengthening effect of the composite nano-precipitates. On the other hand, Er can also form the Al3Er phase with Al. When the Al3Er phase is distributed near the grain boundaries of the α-Al matrix, it can restrict grain boundary migration and inhibit the growth of α-Al matrix grains, making it easier for the aluminum alloy microstructure to remain fine and stable during heat treatment or high-temperature service. When the Al3Er phase or the Er-containing composite nano-precipitates are distributed inside the α-Al matrix grains, they can also hinder local slip and deformation propagation inside the α-Al matrix, thereby improving the strength of the aluminum alloy components. Thus, Er can, to a certain extent, share the strengthening and microstructure stabilization effects that originally needed to be provided by Sc, reducing the dependence of aluminum alloy materials on the high-cost element Sc, and taking into account both the strengthening effect and the manufacturing cost.

[0034] Simultaneously, Er and Sc, when jointly involved in the formation of the Al3(Er,Sc,Zr) composite nanoprecipitates, can enhance the strengthening effect between the composite nanoprecipitates and the α-Al matrix. This is because there is a certain lattice difference between the Er- and Sc-containing composite nanoprecipitates and the α-Al matrix. This lattice difference creates local elastic strain regions around the composite nanoprecipitates, making local slippage and deformation propagation within the α-Al matrix more difficult, thereby further improving the strength of the aluminum alloy components. In other words, Er and Sc not only provide the elemental basis for the formation of the Al3(Er,Sc,Zr) composite nanoprecipitates, but also enhance the precipitation strengthening effect of aluminum alloy materials by strengthening the interaction between the composite nanoprecipitates and the α-Al matrix.

[0035] In the aluminum alloy material of this invention, Zr is mainly used to improve the high-temperature stability of the Al3(Er,Sc,Zr) composite nano-precipitates. It should be noted that although the Al3(Er,Sc,Zr) composite nano-precipitates are formed by the joint participation of Er, Sc, and Zr, the elements within the composite nano-precipitate are not completely uniformly distributed. Instead, due to the differences in the diffusion rates of Er, Sc, and Zr in the α-Al matrix, a core-shell structure with different compositional distributions can be formed. Specifically, during heat treatment, Sc and Er atoms diffuse faster in the α-Al matrix, preferentially aggregating to form nanoscale Al3(Sc,Er) particles, resulting in a relatively Er- and Sc-rich core region in the composite nano-precipitate. Zr diffuses more slowly in the α-Al matrix, and subsequently tends to gradually enrich in the outer region of the composite nano-precipitate, thus forming a relatively Zr-rich outer shell region. The slow diffusion rate of Zr tends to form a Zr-rich shell layer outside the Al3(Sc,Er) core. This dense Zr shell greatly inhibits the outward diffusion of internal Sc and Er atoms and the inward diffusion of α-Al matrix atoms, thereby significantly delaying the coarsening and dissolution of the composite nano-precipitate at high temperatures. As a result, the Al3(Er,Sc,Zr) composite nano-precipitate can still maintain good strengthening and structural stability at higher temperatures.

[0036] Based on this, the present invention, by limiting the weight percentage of Er to 0.6%~0.8%, Sc to 0.5%~0.8%, and Zr to 0.3%~0.4%, enables Er, Sc, and Zr to form a relatively well-matched composite microalloying effect in Al-Ce-based additive manufacturing aluminum alloy materials. Specifically, Er and Sc contribute to the formation and strengthening effect of Al3(Er,Sc,Zr) composite nanoprecipitates, and Er can also partially replace Sc to reduce the dependence of aluminum alloy materials on high-cost Sc. Zr is used to form a Zr-rich shell on the outer layer of the Al3(Er,Sc,Zr) composite nanoprecipitates, improving the anti-coarsening ability and high-temperature stability of the Al3(Er,Sc,Zr) composite nanoprecipitates. If the Er, Sc, or Zr content is too low, it will be difficult to form a sufficient amount of stable Al3(Er,Sc,Zr) composite nano-precipitates, making it difficult to fully improve the strength and high-temperature microstructure stability of aluminum alloy components. If the Er, Sc, or Zr content is too high, it may lead to the formation of coarse precipitates or segregation structures, affecting the uniformity of the aluminum alloy microstructure and the elongation of the aluminum alloy components. Therefore, by synergistically controlling the Er, Sc, and Zr content ranges mentioned above, it is helpful to improve the tensile mechanical properties at 25℃, the high-temperature tensile mechanical properties, and the high-temperature service stability of aluminum alloy components.

[0037] Furthermore, this invention controls the volume fraction of particles with a diameter in the range of 15μm to 70μm in the aluminum alloy material to be ≥90%. For aluminum alloy materials, particle size distribution directly affects powder spreading uniformity, powder flowability, and laser melting stability. If the proportion of fine powder in the aluminum alloy material is too high, powder flowability decreases, easily leading to problems such as agglomeration, uneven powder spreading, and increased oxidation risk. If the proportion of coarse powder in the aluminum alloy material is too high, problems such as insufficient melting, lack of fusion, or decreased molten pool stability easily occur during laser melting. Based on this, this invention, by controlling the volume fraction of particles with a diameter in the range of 15μm to 70μm in the aluminum alloy material to be ≥90%, enables the aluminum alloy material to possess both good powder spreading performance and laser melting adaptability, reducing forming defects such as porosity, lack of fusion, and cracks, thereby improving the forming density and mechanical property stability of aluminum alloy components.

[0038] Therefore, this invention achieves synergistic effects among the alloy components by controlling the weight percentages of Ce, Er, Sc, and Zr, and by controlling the volume fraction of the aluminum alloy material within the particle size range of 15 μm to 70 μm. Ce, in particular, contributes to the formation of highly thermally stable Al. 11The Ce3 and Al2Ce phases pin grain boundaries and improve near-eutectic solidification characteristics, thereby reducing hot cracking susceptibility. Er and Sc synergistically form Al3(Er,Sc,Zr) composite nanoprecipitates, where the relatively fast-diffusion Er and Sc contribute to the formation of Er-rich and Sc-rich cores, while Zr, due to its slow diffusion, forms a dense Zr-rich shell outside the core, thus forming a core-shell composite nanoprecipitate. This helps suppress the diffusion of Sc and Er atoms, significantly delaying the high-temperature coarsening of the precipitates. In addition, a suitable particle size distribution helps improve powder spreading uniformity and laser melting stability, reducing forming defects such as porosity, lack of fusion, and cracks. Therefore, the aluminum alloy material of this invention, after additive manufacturing, can achieve high-density forming while maintaining good tensile mechanical properties at 25°C and high-temperature tensile mechanical properties, thereby meeting the application requirements of lightweight, high-reliability, and high-temperature service stability aluminum alloy components in aerospace, defense, high-end transportation, and new energy vehicle fields.

[0039] In some embodiments, the weight ratio of Er to Sc is (0.8~1.5):1. By further controlling the weight ratio of Er to Sc, the roles of Er and Sc in the Al3(Er,Sc,Zr) composite nano-precipitates can be more matched. On the one hand, an appropriate amount of Sc helps to ensure the strengthening effect of the composite nano-precipitates on the α-Al matrix; on the other hand, an appropriate amount of Er helps to participate in the formation of the composite nano-precipitates together with Sc, and to a certain extent shares the strengthening and microstructure stabilizing role undertaken by Sc. Therefore, controlling the weight ratio of Er to Sc helps to reduce the dependence of aluminum alloy materials on high-cost Sc elements while ensuring the strength and high-temperature microstructure stability of aluminum alloy components, thus balancing mechanical properties and manufacturing costs. Specifically, the weight ratio of Er to Sc can be 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, or any combination thereof.

[0040] In some embodiments, the volume distribution D10 particle size of the aluminum alloy material is 15 μm to 25 μm, the volume distribution D50 particle size is 30 μm to 40 μm, and the volume distribution D90 particle size is 55 μm to 70 μm. By further controlling the volume distributions D10, D50, and D90 of the aluminum alloy material, a more concentrated particle size distribution can be achieved. A volume distribution D10 within the above range helps reduce agglomeration, oxidation, and decreased flowability caused by excessively fine powder; a volume distribution D50 within the above range helps ensure that the bulk powder particle size matches the powder spreading thickness and melting capacity during selective laser melting; and a volume distribution D90 within the above range helps reduce incomplete melting, lack of fusion, and decreased melt pool stability caused by excessively coarse powder. Therefore, controlling these particle size distribution parameters helps to further improve powder spreading uniformity and laser melting stability, thereby improving the forming density and mechanical property consistency of the aluminum alloy components. Specifically, the volume distribution D10 of the aluminum alloy material can be a range of 15μm, 18μm, 20μm, 22μm, 25μm or any two of these; the volume distribution D50 can be a range of 30μm, 32μm, 35μm, 38μm, 40μm or any two of these; and the volume distribution D90 can be a range of 55μm, 58μm, 60μm, 63μm, 66μm, 70μm or any two of these.

[0041] In some embodiments, the sphericity of the aluminum alloy material is ≥80%, and the hollow powder ratio is ≤1%. The sphericity can be determined by image analysis, specifically: acquiring images of the aluminum alloy powder particles, statistically analyzing the projected area and perimeter of at least 10,000 powder particles, and applying the formula S=4πA / P. 2The sphericity of a single powder particle is calculated by multiplying the result by 100%, where S is the sphericity of a single powder particle, A is the projected area of ​​a single powder particle, and P is the projected perimeter of a single powder particle. The sphericity of the aluminum alloy material is the arithmetic mean of the sphericity of the statistically analyzed powder particles. The hollow powder ratio can be determined using a powder cross-sectional image statistical method. Specifically, after embedding and polishing the aluminum alloy material, a powder cross-sectional image is obtained. The number of hollow powder particles in at least 3000 powder particles is counted, and the hollow powder ratio is calculated using the formula H = Nh / N × 100%, where H is the hollow powder ratio, Nh is the number of hollow powder particles, and N is the total number of statistically analyzed powder particles. By controlling the sphericity and hollow powder ratio of the aluminum alloy material, a higher sphericity helps improve powder flowability and powder spreading uniformity, making it easier for the powder to form a uniform and continuous powder layer during spreading, thereby improving the stability of the laser melting process. A lower hollow powder ratio helps reduce the risk of internal cavities in the powder transforming into porosity defects after laser melting. Therefore, by simultaneously controlling sphericity and hollow powder ratio, it is helpful to improve the formability of aluminum alloy materials, reduce forming defects such as porosity and incomplete fusion, thereby improving the forming density and mechanical property stability of aluminum alloy components.

[0042] In some embodiments, the oxygen content of the aluminum alloy material is ≤300ppm and the nitrogen content is ≤20ppm. Excessive oxygen and nitrogen content can easily lead to the formation of oxides, nitrides, or other inclusions on the powder surface or in the aluminum alloy microstructure, affecting powder melting stability and molten pool flow, and potentially becoming inducing sites for defects such as porosity and cracks. Therefore, controlling the oxygen and nitrogen content in the aluminum alloy material helps improve powder cleanliness, reduce the risk of inclusion defects during additive manufacturing, and enable aluminum alloy components to achieve higher forming density and more stable mechanical properties.

[0043] In a second aspect, the present invention provides a method for preparing an aluminum alloy material, comprising the following steps: S1, mixing the raw materials for forming the aluminum alloy material according to a ratio to obtain a mixture; S2, subjecting the mixture to a melting process, a refining process, an atomization process, and a cooling process in sequence to obtain aluminum alloy powder; S3, sieving the aluminum alloy powder to obtain the aluminum alloy material.

[0044] Specifically, in step S1, by mixing the raw materials used to form the aluminum alloy material according to the target composition ratio, the amount of Ce, Er, Sc, Zr and Al added can be controlled from the raw material end, so that the alloy composition of the obtained aluminum alloy material meets the preset composition requirements, thereby providing a compositional basis for the subsequent formation of Ce heat-resistant strengthening phase and Al3(Er,Sc,Zr) composite nano-precipitated phase.

[0045] In step S2, the mixed raw materials are smelted to fully melt each material and form a relatively homogeneous alloy melt. Refining the alloy melt reduces inclusions and gas content, improving its cleanliness. Atomizing the refined alloy melt breaks it into fine droplets, which then rapidly solidify into aluminum alloy powder during flight and cooling. Cooling after atomization ensures the aluminum alloy powder is sufficiently cooled and stabilized, reducing the risk of oxidation, agglomeration, or morphological damage during collection and subsequent processing. Simultaneously, sufficient cooling of the atomized powder further reduces the risk of oxidation, agglomeration, or morphological damage during collection, transfer, or sieving, thus helping to maintain a low oxygen content, high sphericity, and good flowability in the aluminum alloy material. Therefore, step S2 helps improve the compositional uniformity, powder cleanliness, and morphological stability of the aluminum alloy powder.

[0046] In step S3, by sieving the aluminum alloy powder, excessively fine and coarse powders unsuitable for additive manufacturing can be removed, resulting in an aluminum alloy material with a suitable particle size distribution. Therefore, step S3 helps improve the powder flowability, powder spreading uniformity, and laser melting stability of the aluminum alloy material, reducing forming defects such as porosity, incomplete fusion, and cracks in subsequent additive manufacturing processes.

[0047] Therefore, by controlling the raw material ratio in step S1, the melting-refining-gas atomization-cooling treatment in step S2, and the sieving treatment in step S3, this invention can produce aluminum alloy materials with uniform composition, high cleanliness, good morphology, and suitable particle size distribution, thereby providing a stable powder basis for subsequent additive manufacturing processes such as selective laser melting to achieve high-density and low-defect forming.

[0048] In some embodiments of the present invention, the raw materials used to form the aluminum alloy material include Al source, Ce source, Er source, Sc source, and Zr source. Specifically, the Al source may include pure aluminum, the Ce source may include pure cerium, the Er source may include an aluminum-erbium master alloy, the Sc source may include an aluminum-scandium master alloy, and the Zr source may include an aluminum-zirconium master alloy. Using the above-mentioned raw material forms helps to improve the stability and compositional controllability of the addition of elements such as Ce, Er, Sc, and Zr, making it easier to control the weight percentage of each element in the resulting aluminum alloy material within a preset range. Specifically, the purity of pure aluminum is ≥99.9%; the purity of pure cerium is ≥99.9%; the weight percentage of erbium in the aluminum-erbium master alloy is 5%, and the purity is ≥99%; the weight percentage of scandium in the aluminum-scandium master alloy is 5%, and the purity is ≥99%; and the weight percentage of zirconium in the aluminum-zirconium master alloy is 10%, and the purity is ≥99%.

[0049] In some embodiments, the melting temperature is 750°C to 800°C, and the melting time is 20 min to 30 min; and / or, the refining temperature is 1000°C to 1050°C, and the refining time is 15 min to 20 min; and / or, the atomization temperature is 850°C to 900°C, and the atomization pressure is 2.0 MPa to 3.3 MPa. By controlling the melting temperature and time, it is helpful to ensure that raw materials such as Al, Ce, Er, Sc, and Zr are fully melted and mixed uniformly, reducing insufficient melting and compositional inhomogeneity caused by excessively low melting temperature or short melting time. It can also mitigate problems such as element burn-off, melt oxidation, or increased energy consumption caused by excessively high melting temperature or long melting time, thereby improving the compositional stability of the alloy melt and the compositional consistency of the final powder. Specifically, the melting temperature can be a range of 750°C, 760°C, 770°C, 780°C, 790°C, 800°C or any combination thereof; the melting time can be a range of 20 min, 22 min, 25 min, 28 min, 30 min or any combination thereof.

[0050] By controlling the refining temperature and time, the uniform distribution of elements in the alloy melt can be further promoted, and the inclusions and gas content in the alloy melt can be reduced, thereby improving the purity of the alloy melt. This helps to reduce inclusion defects and gas-related defects in the powder, increase the powder weight of the aluminum alloy material, and improve the forming density and mechanical property stability of the aluminum alloy components. Specifically, the refining temperature can be within the range of 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, or any combination thereof; the refining time can be within the range of 15min, 16min, 18min, 20min, or any combination thereof.

[0051] By controlling the atomization temperature within the aforementioned range, the alloy melt can maintain suitable fluidity and atomization stability. By controlling the atomization pressure within the aforementioned range, the alloy melt can be fully broken down under the action of the atomizing gas, forming powder particles with suitable particle size distribution and high sphericity. This helps to improve the powder weight of aluminum alloy materials and their adaptability to additive manufacturing. Specifically, the atomization temperature can be within the range of 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, or any combination thereof; the atomization pressure can be within the range of 2.0MPa, 2.2MPa, 2.5MPa, 2.8MPa, 3.0MPa, 3.3MPa, or any combination thereof.

[0052] In some embodiments of the present invention, high-purity argon gas is used as the atomizing gas for the atomization process. High-purity argon gas can reduce the risk of oxidation of the alloy melt and powder particles during gas atomization, and helps to control the oxygen and nitrogen content of the aluminum alloy material, thereby improving powder cleanliness and subsequent additive manufacturing forming weight. Specifically, the purity of the high-purity argon gas is ≥99.9%.

[0053] In some embodiments of the present invention, step S3 involves using an ultrasonic vibrating screen to sieve the aluminum alloy powder. Sieving with an ultrasonic vibrating screen reduces fine powder agglomeration and screen clogging, improves sieving efficiency and consistency, and thus obtains aluminum alloy materials with a particle size distribution that meets the requirements of additive manufacturing. This helps ensure that the volume fraction of the obtained aluminum alloy material in the 15μm~70μm particle size range meets preset requirements, improves powder spreading uniformity and laser melting stability, and reduces forming defects such as porosity, incomplete fusion, and cracks.

[0054] In some embodiments of the present invention, the method for preparing aluminum alloy materials further includes a cleaning process prior to step S1. This cleaning process includes wiping the inner wall of the gas atomization device, the crucible, and the tundish with ethanol. This cleaning process reduces the contamination of the alloy melt by residual impurities, moisture, or oxides in the inner wall of the gas atomization device, the crucible, and the tundish, thereby reducing the oxygen content and inclusion content of the powder and improving the cleanliness of the aluminum alloy material.

[0055] In some embodiments of the present invention, when placing the raw materials in the crucible, they are distributed according to the principle of looser distribution at the top and denser distribution at the bottom. By adopting the method of looser distribution at the top and denser distribution at the bottom, the problem of bridging structures between raw materials during the melting process, which leads to local raw materials being unable to fall or fully melt, can be reduced, thereby helping to improve the compositional uniformity of the alloy melt and the compositional consistency of the final powder.

[0056] In some embodiments of the present invention, the melting chamber and atomization chamber are subjected to a sealing test before the melting process. When the vacuum degree of the melting chamber and atomization chamber reaches a preset vacuum degree, the airtightness is considered to be satisfactory. By performing a sealing test, the entry of external air into the device during the melting and atomization processes can be reduced, lowering the risk of oxidation, gas absorption, or introduction of impurities into the alloy melt, thereby contributing to the acquisition of low-oxygen, low-nitrogen, and compositionally stable aluminum alloy materials. Specifically, the preset vacuum degree can be a range of 40 Pa, 45 Pa, 50 Pa, 55 Pa, 60 Pa, or any combination thereof.

[0057] In some embodiments of the present invention, after the sealing test is passed, the melting chamber and atomization chamber are purged with high-purity argon gas before melting. Purging with high-purity argon gas reduces the oxygen and nitrogen content in the melting and atomization chambers, decreasing the likelihood of the alloy melt coming into contact with oxygen and nitrogen during melting, refining, and gas atomization. This reduces the oxygen and nitrogen content in the aluminum alloy material, improving powder weight and subsequent additive manufacturing stability.

[0058] A third aspect of the present invention provides a method for preparing an aluminum alloy component, the method comprising: using the aluminum alloy material described above, or the aluminum alloy material prepared by the method described above, and sequentially performing 3D printing and heat treatment to obtain the aluminum alloy component.

[0059] Selective laser melting (SLM) of aluminum alloy was used to form the printed component, followed by heat treatment to obtain an aluminum alloy part. Due to the suitable composition and particle size distribution of aluminum alloy, it exhibits good powder spreading performance, laser melting stability, and low thermal cracking sensitivity during SLM, thus contributing to the acquisition of a highly dense, low-defect printed component. Heat treatment promotes the formation or stabilization of Al3(Er,Sc,Zr) composite nano-precipitates and Al3Er phases, further improving the strength and high-temperature structural stability of the aluminum alloy component. This contributes to giving the aluminum alloy component both good mechanical properties at 25℃ and high-temperature mechanical properties.

[0060] In some embodiments, 3D printing is performed in an atmosphere with an oxygen content ≤0.05%; and / or, the 3D printing pressure is 23mbar~27mbar, and the fan flow rate is 2.5m / s~3.0m / s; and / or, the substrate preheating temperature is 80℃~150℃; and / or, the 3D printing layer thickness is 20μm~50μm, and the interlayer rotation angle is 67°; and / or, the laser scanning spacing is 90μm~110μm, the laser scanning power is 250W~330W, and the laser scanning speed is 1000mm / s~2000mm / s. By controlling the oxygen content in the printing chamber within the aforementioned range, it helps reduce powder and molten pool oxidation, lowering the risk of oxidation inclusion defects. Controlling the printing chamber pressure and fan velocity helps stabilize the protective atmosphere and promptly remove smoke and splash particles, reducing their interference with the stability of the powder layer and molten pool. This contributes to improving the stability of the selective laser melting process, reducing defects such as porosity, inclusions, and uneven melting, and increasing the forming density of aluminum alloy components. Specifically, the printing chamber pressure can be within the range of 23 mbar, 24 mbar, 25 mbar, 26 mbar, 27 mbar, or any combination thereof; the fan velocity can be within the range of 2.5 m / s, 2.6 m / s, 2.7 m / s, 2.8 m / s, 2.9 m / s, 3.0 m / s, or any combination thereof.

[0061] Preheating the substrate reduces the temperature gradient between the molten pool and the surrounding area during forming, mitigating thermal stress concentration caused by rapid solidification and repeated thermal cycling, thereby reducing the risk of crack formation. This helps improve the low-defect forming capability in additive manufacturing and enhances the forming weight and mechanical property stability of aluminum alloy components. Specifically, the substrate preheating temperature can be within the range of 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or any combination thereof.

[0062] By controlling the layer thickness and scanning spacing in 3D printing, it is possible to match the thickness of individual powder layers, the overlap of adjacent melt channels, and the laser melting capability, thereby reducing defects such as incomplete fusion and melting. A layer rotation angle of 67° helps reduce the repeated superposition of heat input and microstructure orientation between consecutive layers, improving the uniformity of the formed microstructure and reducing anisotropy. This contributes to improving the forming density and overall mechanical properties of aluminum alloy components. Specifically, the layer thickness in 3D printing can be 20μm, 30μm, 40μm, 45μm, 50μm, or any combination thereof; the scanning spacing can be 90μm, 98μm, 100μm, 105μm, 110μm, or any combination thereof.

[0063] By controlling the scanning power and scanning speed, the laser energy input can be matched with the melting characteristics of the aluminum alloy material, forming a more stable molten pool. Insufficient energy input can easily lead to defects such as incomplete melting and lack of fusion; excessive energy input can cause molten pool fluctuations, increased spatter, element burn-off, or a higher risk of porosity formation. Therefore, the aforementioned scanning parameters help improve laser melting stability, reduce forming defects, and thus improve the forming density and mechanical property stability of aluminum alloy components. Specifically, the scanning power for 3D printing can be within the range of 250W, 260W, 280W, 300W, 320W, 330W, or any combination thereof; the scanning speed can be within the range of 1000mm / s, 1200mm / s, 1400mm / s, 1600mm / s, 1800mm / s, 2000mm / s, or any combination thereof.

[0064] In some embodiments, the heat treatment temperature is 320℃~350℃, and the heat treatment time is 4h~7h. By controlling the temperature and time of the heat treatment, it is possible to promote the formation of Al3(Er,Sc,Zr) composite nanoprecipitates of Er, Sc, and Zr in the α-Al matrix and further stabilize the microstructure of the aluminum alloy, thereby improving the strength and high-temperature microstructure stability of the aluminum alloy component. Simultaneously, heat treatment can also release residual stress formed during additive manufacturing to a certain extent, which helps improve the mechanical property stability of the aluminum alloy component. Therefore, the heat-treated aluminum alloy component can maintain good tensile mechanical properties at both 25℃ and high-temperature conditions. Specifically, the heat treatment temperature can be a range of 320℃, 330℃, 340℃, 345℃, 350℃, or any combination thereof; the heat treatment time can be a range of 4h, 5h, 5.5h, 6h, 7h, or any combination thereof.

[0065] In a fourth aspect, the present invention provides an aluminum alloy component, which is prepared by the above-described method for preparing aluminum alloy components; wherein the aluminum alloy component has a tensile strength of 520 MPa to 550 MPa at 25°C, a yield strength of 440 MPa to 460 MPa at 25°C, and an elongation of 10.5% to 13.5% at 25°C; a tensile strength of 250 MPa to 280 MPa at 300°C, a yield strength of 230 MPa to 260 MPa at 300°C, and an elongation of 16.2% to 18.3% at 300°C; and a tensile strength of 180 MPa to 200 MPa at 400°C, a yield strength of 150 MPa to 180 MPa at 400°C, and an elongation of 16.5% to 19.2% at 400°C.

[0066] Because this aluminum alloy component is simultaneously subjected to the combined effects of a heat-resistant strengthening phase formed by Ce, an Al3(Er,Sc,Zr) composite nano-precipitate formed by Er, Sc, and Zr, and a highly dense and formable microstructure, it exhibits high yield strength, tensile strength, and elongation at 25°C, and maintains good strength and ductility at high temperatures such as 300°C and 400°C. Therefore, this aluminum alloy component is suitable for structural parts requiring lightweight design, high strength, and high-temperature service stability.

[0067] In some embodiments of the present invention, the density of the aluminum alloy component is ≥99.9%. Higher density indicates fewer internal defects such as porosity, lack of fusion, and cracks in the aluminum alloy component, reducing the disruption of load-bearing continuity caused by these defects, thereby contributing to improved strength, elongation, and mechanical property stability of the aluminum alloy component. Therefore, aluminum alloy components with a density ≥99.9% are more conducive to meeting the application requirements of high-reliability load-bearing components in fields such as aerospace, defense, high-end transportation, and new energy vehicles.

[0068] In a fifth aspect, the present invention provides an aerospace material comprising the aluminum alloy component described above or an aluminum alloy component prepared by the method described above.

[0069] Because the aforementioned aluminum alloy components possess low density, high mechanical properties at 25°C, good high-temperature mechanical properties, and high formability density, they can meet the requirements of aerospace materials for lightweighting, high reliability, and high-temperature service stability. Therefore, using these aluminum alloy components in aerospace materials helps improve the load-bearing stability and reliability of related structural components in complex service environments.

[0070] The present invention will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention.

[0071] Example 1

[0072] I. The preparation method of the aluminum alloy material in this embodiment includes the following steps:

[0073] S0, before adding materials, wipe the inner wall of the atomizing device, crucible and intermediate package with ethanol.

[0074] S1, Weigh the raw materials used to form the aluminum alloy material according to the proportions and place them in a crucible to obtain a mixed raw material; wherein, the material distribution follows the principle of sparse at the top and dense at the bottom;

[0075] The raw materials include pure aluminum, pure cerium, aluminum-erbium master alloy, aluminum-scandium master alloy, and aluminum-zirconium master alloy. Among them, the purity of pure aluminum and pure cerium is ≥99.99%; the erbium weight percentage in the aluminum-erbium master alloy is 5%, with a purity ≥99%; the scandium weight percentage in the aluminum-scandium master alloy is 5%, with a purity ≥99%; and the zirconium weight percentage in the aluminum-zirconium master alloy is 10%, with a purity ≥99%.

[0076] S2. The sealing performance of the melting chamber and atomization chamber is tested. When the vacuum level in both chambers reaches approximately 50 Pa, the airtightness is considered satisfactory. After achieving the airtightness standard, the melting chamber and atomization chamber are purged with high-purity argon. Then, the mixture is sequentially melted at 780℃ for 30 minutes and refined at 1000℃ for 20 minutes to obtain an aluminum alloy melt. The resulting aluminum alloy melt is poured into an intermediate ladle and atomized at 860℃ using high-purity argon as the atomizing gas at a pressure of 2.5 MPa. After atomization, the resulting aluminum alloy powder is allowed to cool down to obtain aluminum alloy powder.

[0077] S3, pour the aluminum alloy powder into an ultrasonic vibrating screen for particle size sieving to obtain the aluminum alloy material of this embodiment.

[0078] The aluminum alloy material prepared in this embodiment has the following composition and weight percentages: Ce: 9.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.3%, with the balance being Al and unavoidable impurities. The weight ratio of Er to Sc is 1.0:1.

[0079] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 95.43%, the volume distribution D10 is 22.3μm, the volume distribution D50 is 36.9μm, the volume distribution D90 is 63.7μm, and the powder yield is 40%; the oxygen content is 111ppm, the nitrogen content is 12ppm; the sphericity is 88.4%, and the hollow powder rate is 0.89%.

[0080] II. The method for preparing the aluminum alloy component in this embodiment includes:

[0081] Using the aluminum alloy material obtained in this embodiment, laser powder deposition additive manufacturing technology was used to print the part, resulting in a printed component. Specifically, the oxygen content in the printing chamber was 0.03%, the pressure in the printing chamber was 24 mbar, the fan speed was 2.5 m / s, the substrate preheating temperature was 110℃, the printing layer thickness was 30 μm, the scanning spacing was 100 μm, the interlayer rotation angle was 67°, the scanning power was 315 W, and the scanning speed was 1600 mm / s.

[0082] After printing, the printed component is heat-treated at a temperature of 325°C for 6 hours to obtain the aluminum alloy component of this embodiment.

[0083] Example 2

[0084] The difference between this embodiment and Embodiment 1 is that:

[0085] I. The composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 10.0%, Er: 0.7%, Sc: 0.5%, Zr: 0.3%, with the balance being Al and unavoidable impurities. The weight ratio of Er to Sc is 1.4:1.

[0086] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 93.25%, the volume distribution D10 is 22.3μm, the volume distribution D50 is 38.5μm, the volume distribution D90 is 66.5μm, and the powder yield is 37%; the oxygen content is 95ppm, the nitrogen content is 13ppm; the sphericity is 85.5%, and the hollow powder rate is 0.93%.

[0087] II. In the aluminum alloy component preparation method of this embodiment, the pressure in the printing chamber during the selective laser melting forming process is 26 mbar.

[0088] Example 3

[0089] The difference between this embodiment and Embodiment 1 is that the composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 6.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.3%, with the balance being Al and unavoidable impurities.

[0090] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 94.11%, the volume distribution D10 is 22.6μm, the volume distribution D50 is 37.3μm, the volume distribution D90 is 65.2μm, and the powder yield is 35%; the oxygen content is 135ppm, the nitrogen content is 15ppm; the sphericity is 87.2%, and the hollow powder rate is 0.87%.

[0091] Example 4

[0092] The difference between this embodiment and Embodiment 1 is that the composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 11.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.3%, with the balance being Al and unavoidable impurities.

[0093] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 95.31%, the volume distribution D10 is 21.5μm, the volume distribution D50 is 33.8μm, the volume distribution D90 is 61.3μm, and the powder yield is 36%; the oxygen content is 128ppm, the nitrogen content is 18ppm; the sphericity is 83.8%, and the hollow powder rate is 0.83%.

[0094] Example 5

[0095] The difference between this embodiment and Embodiment 1 is that the composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 9.0%, Er: 0.6%, Sc: 0.75%, Zr: 0.3%, with the balance being Al and unavoidable impurities. The weight ratio of Er to Sc is 0.8:1.

[0096] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 94.83%, the volume distribution D10 is 22.2μm, the volume distribution D50 is 35.2μm, the volume distribution D90 is 59.8μm, and the powder yield is 34.5%; the oxygen content is 105ppm, the nitrogen content is 17ppm; the sphericity is 85.7%, and the hollow powder rate is 0.81%.

[0097] Example 6

[0098] The difference between this embodiment and Embodiment 1 is that the composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 9.0%, Er: 0.75%, Sc: 0.5%, Zr: 0.3%, with the balance being Al and unavoidable impurities. The weight ratio of Er to Sc is 1.5:1.

[0099] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 96.35%, the volume distribution D10 is 19.8μm, the volume distribution D50 is 33.5μm, the volume distribution D90 is 58.6μm, and the powder yield is 35.5%; the oxygen content is 98ppm, the nitrogen content is 15ppm; the sphericity is 87.3%, and the hollow powder rate is 0.92%.

[0100] Example 7

[0101] The difference between this embodiment and Embodiment 1 is that the composition and weight percentage of the aluminum alloy material prepared in this embodiment are Ce: 9.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.4%, with the balance being Al and unavoidable impurities.

[0102] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 93.55%, the volume distribution D10 is 20.5μm, the volume distribution D50 is 34.3μm, the volume distribution D90 is 60.8μm, and the powder yield is 36.8%; the oxygen content is 118ppm, the nitrogen content is 19ppm; the sphericity is 88.4%, and the hollow powder rate is 0.85%.

[0103] Example 8

[0104] The difference between this embodiment and embodiment 1 is that in this embodiment, in step S2, the melting process is carried out at 750°C for 20 minutes, the refining process is carried out at 1000°C for 15 minutes, and the atomization process is carried out at 850°C. The pressure of the atomization process is 2.0 MPa.

[0105] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 92.51%, the volume distribution D10 is 22.8μm, the volume distribution D50 is 36.5μm, the volume distribution D90 is 64.4μm, and the powder yield is 34.9%; the oxygen content is 143ppm, the nitrogen content is 16ppm; the sphericity is 83.5%, and the hollow powder rate is 0.79%.

[0106] Example 9

[0107] The difference between this embodiment and embodiment 1 is that in this embodiment, in step S2, the melting process is carried out at 800°C for 30 minutes, the refining process is carried out at 1050°C for 20 minutes, and the atomization process is carried out at 900°C. The pressure of the atomization process is 3.3 MPa.

[0108] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 94.71%, the volume distribution D10 is 22.8μm, the volume distribution D50 is 37.5μm, the volume distribution D90 is 64.3μm, and the powder yield is 38.5%; the oxygen content is 124ppm, the nitrogen content is 20ppm; the sphericity is 90.4%, and the hollow powder rate is 0.88%.

[0109] Example 10

[0110] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the oxygen content in the printing chamber is 0, the pressure in the printing chamber is 23 mbar, the fan flow rate is 2.5 m / s, the substrate preheating temperature is 80℃, the printing layer thickness is 30 μm, the scanning spacing is 100 μm, the interlayer rotation angle is 67°, the scanning power is 250 W, and the scanning speed is 1000 mm / s.

[0111] Example 11

[0112] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the oxygen content in the printing chamber is 0.05%, the pressure in the printing chamber is 27 mbar, the fan flow rate is 3.0 m / s, the substrate preheating temperature is 150℃, the printing layer thickness is 30 μm, the scanning spacing is 100 μm, the interlayer rotation angle is 67°, the scanning power is 330 W, and the scanning speed is 2000 mm / s.

[0113] Example 12

[0114] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the heat treatment temperature is 320℃ and the heat treatment time is 4h.

[0115] Example 13

[0116] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the heat treatment temperature is 330℃ and the heat treatment time is 7h.

[0117] Example 14

[0118] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the printing chamber pressure is 25 mbar, the fan flow rate is 2.8 m / s, the substrate preheating temperature is 100℃, the scanning spacing is 90 μm, the scanning power is 350 W, and the scanning speed is 2200 mm / s.

[0119] Example 15

[0120] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the heat treatment temperature is 350℃ and the heat treatment time is 8h.

[0121] Example 16

[0122] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the aging heat treatment temperature is 325℃ and the aging heat treatment time is 2h.

[0123] Example 17

[0124] The difference between this embodiment and Embodiment 1 is that in the preparation method of the aluminum alloy component in this embodiment, the printed component is not heat-treated after printing.

[0125] Example 18

[0126] The difference between this embodiment and Embodiment 1 is that the aluminum alloy material prepared in this embodiment has the following composition and weight percentages: Ce: 9.0%, Er: 0.6%, Sc: 0.8%, Zr: 0.3%, with the balance being Al and unavoidable impurities. The weight ratio of Er to Sc is 0.75:1.

[0127] In the aluminum alloy material obtained in this embodiment, the volume fraction of particles with a particle size in the range of 15μm to 70μm is 92.83%, the volume distribution D10 is 19.2μm, the volume distribution D50 is 35.1μm, the volume distribution D90 is 61.5μm, and the powder yield is 31%; the oxygen content is 165ppm, the nitrogen content is 55ppm, the sphericity is 83.1%, and the hollow powder rate is 0.96%.

[0128] Comparative Example 1

[0129] The difference between this comparative example and Example 1 is that the composition and weight percentage of the aluminum alloy material prepared in this comparative example are Ce: 5.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.3%, with the balance being Al and unavoidable impurities.

[0130] In the aluminum alloy material obtained in this comparative example, the volume fraction of particles with a particle size in the range of 15μm to 70μm was 94.15%, the volume distribution D10 was 18.9μm, the volume distribution D50 was 34.9μm, the volume distribution D90 was 58.1μm, and the powder yield was 31.5%; the oxygen content was 151ppm, the nitrogen content was 46ppm; the sphericity was 81.2%, and the hollow powder rate was 0.97%.

[0131] Comparative Example 2

[0132] The difference between this comparative example and Example 1 is that the composition and weight percentage of the aluminum alloy material prepared in this comparative example are Ce: 9.0%, Er: 0.6%, Sc: 0.2%, Zr: 0.3%, with the balance being Al and unavoidable impurities.

[0133] In the aluminum alloy material obtained in this comparative example, the volume fraction of particles with a particle size in the range of 15μm to 70μm was 93.22%, the volume distribution D10 was 19.1μm, the volume distribution D50 was 33.2μm, the volume distribution D90 was 56.9μm, and the powder yield was 32%; the oxygen content was 168ppm, the nitrogen content was 51ppm, the sphericity was 80.9%, and the hollow powder rate was 0.99%.

[0134] Comparative Example 3

[0135] The difference between this comparative example and Example 1 is that the composition and weight percentage of the aluminum alloy material prepared in this comparative example are Ce: 9.0%, Er: 0.6%, Sc: 0.6%, Zr: 0.1%, with the balance being Al and unavoidable impurities.

[0136] In the aluminum alloy material obtained in this comparative example, the volume fraction of particles with a particle size in the range of 15μm to 70μm was 91.52%, the volume distribution D10 was 17.6μm, the volume distribution D50 was 31.1μm, the volume distribution D90 was 55.8μm, and the powder yield was 31%; the oxygen content was 175ppm, the nitrogen content was 59ppm, the sphericity was 81.5%, and the hollow powder rate was 0.97%.

[0137] Comparative Example 4

[0138] The difference between this comparative example and Example 1 is that the volume fraction of particles with a particle size in the range of 15μm to 70μm in the aluminum alloy material is 80% to 85%, while the other conditions are the same as in Example 1.

[0139] Test methods

[0140] The aluminum alloy materials and aluminum alloy components prepared in Examples 1-18 and Comparative Examples 1-4 were subjected to relevant performance tests.

[0141] 1. Tensile properties at 25℃: The tensile properties of the aluminum alloy components obtained in each embodiment and comparative example were tested according to the GB / T 228.1 test standard to obtain the tensile strength, yield strength and elongation at 25℃.

[0142] 2. High-temperature tensile properties: According to the GB / T 228.2 test standard, the high-temperature tensile properties of the aluminum alloy components obtained in each embodiment and comparative example were tested at 300℃ and 400℃ to obtain the tensile strength, yield strength and elongation at the corresponding temperatures.

[0143] The test results are shown in Table 1.

[0144] Table 1

[0145]

[0146] Figure 1 This is an optical microscope metallographic image of the aluminum alloy component obtained in Embodiment 2 of the present invention; Figure 2 This is an optical microscope metallographic image of the aluminum alloy component obtained in Embodiment 6 of the present invention. According to... Figure 1 and Figure 2It can be seen that the cross-sectional microstructure of the aluminum alloy components obtained in Examples 2 and 6 is relatively uniform and has fewer pore defects. This indicates that when the weight percentages of Ce, Er, Sc and Zr are within a suitable range and the volume fraction of the aluminum alloy material in the 15μm~70μm particle size range is relatively high, the obtained aluminum alloy material can be well adapted to the laser powder spreading additive manufacturing process and obtain aluminum alloy components with a relatively dense microstructure.

[0147] Figure 3 This is an optical microscope metallographic image of the aluminum alloy component obtained in Embodiment 14 of the present invention. (Combined with...) Figure 3 It can be seen that the aluminum alloy component obtained in Example 14 has a large number of pore defects. The difference between Example 14 and Example 1 is that the scanning power in Example 14 is 350W and the scanning speed is 2200mm / s. This shows that when the scanning power and scanning speed are too high, it is easy to affect the stability of the molten pool, which will increase the number of pore defects in the aluminum alloy component, thereby reducing the forming density and mechanical properties of the aluminum alloy component.

[0148] Figure 4 This is an optical microscope metallographic image of the aluminum alloy component obtained in Embodiment 18 of the present invention. Combined with... Figure 4 It can be seen that a certain number of pore defects can be observed in the aluminum alloy component obtained in Example 18, and its microstructure density is lower than that of Examples 2 and 6. The difference between Example 18 and Example 1 is that the weight ratio of Er to Sc in Example 18 is 0.75:1. This indicates that when the weight ratio of Er to Sc is too low, it is not conducive to further exerting the synergistic effect of Er and Sc in the Al3(Er,Sc,Zr) composite nano-precipitates, thereby affecting the microstructure stability and high-temperature mechanical properties of the aluminum alloy component.

[0149] Figure 5 This is an optical microscope metallographic image of the aluminum alloy component obtained in Comparative Example 1 of this invention. (Combined with...) Figure 5 It can be seen that the aluminum alloy component obtained in Comparative Example 1 has porosity defects. The difference between Comparative Example 1 and Example 1 is that the weight percentage of Ce in Comparative Example 1 is 5.0%. This indicates that when the Ce content is too low, it is not conducive to the full formation of Al. 11 Heat-resistant strengthening phases such as Ce3 and Al2Ce are not conducive to fully utilizing the Al-Ce system's ability to improve solidification and forming properties, thus leading to a decline in the forming quality and overall mechanical properties of aluminum alloy components.

[0150] Figure 6 This is an optical microscope metallographic image of the aluminum alloy component obtained in Comparative Example 4 of this invention. (Combined with...) Figure 6It can be seen that the aluminum alloy component obtained in Comparative Example 4 has pore defects. The difference between Comparative Example 4 and Example 1 is that the volume fraction of aluminum alloy material in Comparative Example 4 within the particle size range of 15μm to 70μm is only 80% to 85%. This indicates that when the volume fraction of aluminum alloy material within the particle size range of 15μm to 70μm is too low, it is not conducive to the uniform spreading and stable melting of powder in the laser powder spreading additive manufacturing process, and it is easy to generate forming defects such as pores and lack of fusion, thereby reducing the forming density and mechanical properties of aluminum alloy components.

[0151] As shown in Table 1, compared with Comparative Examples 1-4, Examples 1-13, by controlling the weight percentage of Ce in the aluminum alloy material to be 6.0%-11.0%, the weight percentage of Er to be 0.6%-0.8%, the weight percentage of Sc to be 0.5%-0.8%, and the weight percentage of Zr to be 0.3%-0.4%, and by controlling the volume fraction of particles with a particle size in the range of 15μm-70μm to be ≥90%, facilitated the formation of Al. 11 The use of heat-resistant reinforcing phases such as Ce3 and Al2Ce, as well as Al3(Er,Sc,Zr) composite nano-precipitates, improves powder spreading uniformity and laser melting stability, resulting in the following properties in Examples 1-13: 25℃ yield strength ≥440MPa, 25℃ tensile strength ≥521MPa, 25℃ elongation ≥10.5%; 300℃ yield strength ≥230MPa, 300℃ tensile strength ≥252MPa, 300℃ elongation ≥16.2%; 400℃ yield strength ≥151MPa, 400℃ tensile strength ≥180MPa, 400℃ elongation ≥16.5%. Therefore, Examples 1-13 can achieve high mechanical properties at 25℃ while also maintaining good high-temperature mechanical properties at 300℃ and 400℃.

[0152] Comparative Example 1, due to the Ce weight percentage of 5.0%, resulted in Al... 11 The insufficient formation of heat-resistant strengthening phases such as Ce3 and Al2Ce is not conducive to fully utilizing the near-eutectic solidification characteristics of the Al-Ce system to reduce hot cracking sensitivity and improve forming quality. As a result, the aluminum alloy component obtained in Comparative Example 1 has a yield strength of only 399 MPa at 25℃, a tensile strength of only 465 MPa at 25℃, a yield strength of only 94 MPa at 400℃, and a tensile strength of only 115 MPa at 400℃.

[0153] In Comparative Example 2, due to the Sc weight percentage of 0.2%, the degree to which Sc participates in the formation of Al3(Er,Sc,Zr) composite nano-precipitates is insufficient. The strengthening effect of the composite nano-precipitates on the α-Al matrix is ​​reduced, resulting in the aluminum alloy component obtained in Comparative Example 2 having a yield strength of only 402 MPa at 25℃, a tensile strength of only 471 MPa at 25℃, a yield strength of only 198 MPa at 300℃, a tensile strength of only 224 MPa at 300℃, a yield strength of only 85 MPa at 400℃, and a tensile strength of only 109 MPa at 400℃. It is difficult to achieve good mechanical properties at 25℃ and high-temperature mechanical properties.

[0154] In Comparative Example 3, the Zr content was 0.1% by weight, which resulted in insufficient Zr enhancement of the high-temperature stability of the Al3(Er,Sc,Zr) composite nano-precipitates. This was not conducive to the formation of a stable Zr-rich outer layer structure, nor was it conducive to inhibiting the coarsening or dissolution of the composite nano-precipitates under high-temperature conditions. Consequently, the aluminum alloy component obtained in Comparative Example 3 had a yield strength of only 98 MPa and a tensile strength of only 121 MPa at 400℃, indicating a significant decrease in high-temperature mechanical properties.

[0155] In Comparative Example 4, the volume fraction of particles with a diameter in the range of 15μm to 70μm in the aluminum alloy material is 80% to 85%, which makes the powder particle size distribution unsuitable for uniform powder spreading and stable melting in the laser powder spreading additive manufacturing process. This easily leads to defects such as insufficient melting, voids, or lack of fusion. As a result, the aluminum alloy component obtained in Comparative Example 4 has a yield strength of only 359MPa at 25℃, a tensile strength of only 445MPa at 25℃, and an elongation of only 9.5% at 25℃; a yield strength of only 189MPa at 300℃, a tensile strength of only 205MPa at 300℃, and an elongation of only 11.2% at 300℃; and a yield strength of only 62MPa at 400℃, a tensile strength of only 85MPa at 400℃, and an elongation of only 12.3% at 400℃. Its mechanical properties at 25℃ and high-temperature mechanical properties are both poor.

[0156] Furthermore, compared to Example 14, Examples 1-13 further control the laser scanning power of 3D printing to be 250W-330W and the laser scanning speed to be 1000mm / s-2000mm / s. This helps to match the laser energy input with the melting characteristics of the aluminum alloy material, reducing defects such as voids, lack of fusion, and unstable molten pool. As a result, the tensile strength at 25℃ in Examples 1-13 is ≥521MPa, the tensile strength at 300℃ is ≥252MPa, and the tensile strength at 400℃ is ≥180MPa. However, in Example 14, the laser scanning power is 350W and the laser scanning speed is 2200mm / s, both of which are higher than the above preferred ranges. This leads to a decrease in molten pool stability and the formation of more void defects, resulting in a decrease in the tensile strength at 25℃ to 481MPa, the tensile strength at 300℃ to 234MPa, and the tensile strength at 400℃ to 93MPa.

[0157] Compared to Examples 15 and 16, Examples 1-13 further controlled the heat treatment temperature to 320℃-350℃ and the heat treatment time to 4h-7h, avoiding excessively long heat treatment times. This helped promote the formation and stabilization of Al3(Er,Sc,Zr) composite nano-precipitates, while mitigating the problems of coarsening of precipitates or decreased microstructure stability caused by prolonged heat treatment. As a result, Examples 1-13 exhibited better strength and high-temperature mechanical properties. In contrast, Example 15, with a heat treatment time of 8h, was too long, leading to adverse changes in the strengthening microstructure of the aluminum alloy component. Consequently, its tensile strength at 25℃ decreased to 498MPa, and its tensile strength at 400℃ decreased to 115MPa. In Example 16, with a heat treatment time of only 2h, the formation or stabilization of the composite nano-precipitates was insufficient, resulting in a tensile strength of 510MPa at 25℃, 245MPa at 300℃, and 152MPa at 400℃.

[0158] Compared to Example 17, Examples 1-13 further heat-treated the printed components, which helped promote the formation or stabilization of Al3(Er,Sc,Zr) composite nano-precipitates and Al3Er phases as reinforcing structures, and released some of the residual stress formed during additive manufacturing, thereby further improving the strength and high-temperature structural stability of the aluminum alloy components. However, in Example 17, because the printed components were not heat-treated after printing, the formation of reinforcing phases was insufficient, and the strength of the aluminum alloy components decreased significantly, resulting in a yield strength of only 314 MPa at 25°C, a tensile strength of only 424 MPa at 25°C, a yield strength of only 63 MPa at 400°C, and a tensile strength of only 85 MPa at 400°C.

[0159] Compared to Example 18, Examples 1-13 further controlled the weight ratio of Er to Sc to be (0.8-1.5):1, which helped to make the roles of Er and Sc in the Al3(Er,Sc,Zr) composite nano-precipitates more matched, and improved the high-temperature microstructure stability while ensuring precipitation strengthening effect. However, in Example 18, the weight ratio of Er to Sc was 0.75:1 and the nitrogen content was relatively high, which led to a decrease in the synergistic effect between Er and Sc, which was not conducive to further improving the stability of the composite nano-precipitates. As a result, its yield strength at 300℃ decreased to 223MPa, its tensile strength at 300℃ decreased to 248MPa, and its yield strength at 400℃ decreased to 147MPa.

[0160] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art will recognize that the present invention can have various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An aluminum alloy material, characterized in that, The aluminum alloy material comprises, by weight percentage: Ce 6.0%~11.0%, Er 0.6%~0.8%; Sc 0.5%~0.8%, Zr 0.3%~0.4%, with the balance being Al and unavoidable impurities; In the aluminum alloy material, the volume fraction of particles with a particle size in the range of 15μm to 70μm is ≥90%.

2. The aluminum alloy material according to claim 1, characterized in that, The weight ratio of Er to Sc is (0.8~1.5):

1.

3. The aluminum alloy material according to claim 1, characterized in that, The aluminum alloy material has a volume distribution D10 particle size of 15μm~25μm, a volume distribution D50 particle size of 30μm~40μm, and a volume distribution D90 particle size of 55μm~70μm.

4. The aluminum alloy material according to any one of claims 1 to 3, characterized in that, The sphericity of the aluminum alloy material is ≥80%, and the hollow powder content is ≤1%; and / or, The oxygen content of the aluminum alloy material is ≤300ppm and the nitrogen content is ≤20ppm.

5. A method for preparing an aluminum alloy material according to any one of claims 1 to 4, characterized in that, The method for preparing the aluminum alloy material includes the following steps: S1, the raw materials used to form the aluminum alloy material are mixed according to the proportion to obtain a mixture; S2, the mixture is subjected to melting, refining, atomizing and cooling processes in sequence to obtain aluminum alloy powder; S3, the aluminum alloy powder is sieved to obtain the aluminum alloy material.

6. The method for preparing aluminum alloy material according to claim 5, characterized in that, The melting process is carried out at a temperature of 750℃~800℃ for a duration of 20min~30min; and / or, The refining process is carried out at a temperature of 1000℃~1050℃ for a duration of 15min~20min; and / or, The atomization temperature is 850℃~900℃, and the atomization pressure is 2.0MPa~3.3MPa.

7. A method for preparing an aluminum alloy component, characterized in that, The method for preparing the aluminum alloy component includes: using the aluminum alloy material according to any one of claims 1 to 4, or the aluminum alloy material prepared by the method described in claim 5 or 6, and sequentially performing 3D printing and heat treatment to obtain the aluminum alloy component.

8. The method for preparing the aluminum alloy component according to claim 7, characterized in that, The 3D printing is performed in an atmosphere with an oxygen content ≤0.05%; and / or, The 3D printing pressure is 23 mbar to 27 mbar, and the fan velocity is 2.5 m / s to 3.0 m / s; and / or, The preheating temperature of the 3D-printed substrate is 80℃~150℃; and / or, The thickness of the 3D printed layers is 20μm~50μm, and the interlayer rotation angle of the 3D printed layers is 67°; and / or, The laser scanning spacing of the 3D printing is 90μm~110μm, the laser scanning power of the 3D printing is 250W~330W, and the laser scanning speed of the 3D printing is 1000mm / s~2000mm / s; and / or, The heat treatment temperature is 320℃~350℃, and the heat treatment time is 4h~7h.

9. An aluminum alloy component, characterized in that, The aluminum alloy component is prepared using the method for preparing aluminum alloy components as described in claim 7 or 8; The aluminum alloy component has a tensile strength of 520MPa~550MPa at 25℃, a yield strength of 440MPa~460MPa at 25℃, and an elongation of 10.5%~13.5% at 25℃. The aluminum alloy component has a tensile strength of 250MPa~280MPa at 300℃, a yield strength of 230MPa~260MPa at 300℃, and an elongation of 16.2%~18.3% at 300℃. The aluminum alloy component has a tensile strength of 180MPa~200MPa at 400℃, a yield strength of 150MPa~180MPa at 400℃, and an elongation of 16.5%~19.2% at 400℃.

10. An aerospace material, characterized in that, The aerospace material includes the aluminum alloy component as described in claim 9 or the aluminum alloy component prepared by the method described in claim 7 or 8.